Nonlinear spectroscopy of chromophore aggregates with entangled photon pulses - Mukamel S.; Fingerhut B. F.; Dorfman K. E.; Schlawin F. (EPJ Web of Conferences, 2013)
The response of the bacterial reaction center to entangled photons is compared with stochastic and chirped pulses. Nonlinear optical signals reveal how distributions of exciton states may be controlled by quantum light.